2011
DOI: 10.1007/s12149-011-0516-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging discordance between hepatic angiography versus Tc-99m-MAA SPECT/CT: a case series, technical discussion and clinical implications

Abstract: During pre-therapy evaluation for yttrium-90 (Y-90) radioembolization, it is uncommon to find severe imaging discordance between hepatic angiography versus technetium-99m-macroaggregated albumin (Tc-99m-MAA) single photon emission computed tomography with integrated low-dose CT (SPECT/CT). The reasons for severe imaging discordance are unclear, and literature is scarce. We describe 3 patients with severe imaging discordance, whereby tumor angiographic contrast hypervascularity was markedly mismatched to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…Significant differences between vascularization of tumors as assessed during angiography and 99m Tc-MAA uptake on SPECT are described. Therefore, conclusions derived from contrast enhancement of tumors have to be drawn with caution, especially as results derived from angiography and cross-sectional imaging are contradictory in some cases (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences between vascularization of tumors as assessed during angiography and 99m Tc-MAA uptake on SPECT are described. Therefore, conclusions derived from contrast enhancement of tumors have to be drawn with caution, especially as results derived from angiography and cross-sectional imaging are contradictory in some cases (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Other work shows a sensitivity of 100% of using SPECT-CT to detect extrahepatic uptake compared to 41% for non attenuation corrected SPECT and 32% for planar imaging respectively [22]. Recently evaluated also is the discordance between hepatic angiography and MAA SPECT, noting severe discordance in only 3 of 74 cases of patients with HCC [23].…”
Section: Methodsmentioning
confidence: 99%
“…However, different physical properties, surgical procedures and timing between catheterizations result in MAA being an imperfect surrogate for GMS and RMS [23,71,72]. Recent discussions observe that discordance in MAA-microsphere distribution may be attributable to the differing vascularity of HCC and metastases [59], with a suggestion of a more concordant relationship in HCC cases [73].…”
Section: Using 99m Tc-maa As a 90 Y Ms Surrogatementioning
confidence: 99%
See 1 more Smart Citation
“…A discrepancy between the distribution of 99m Tc-MAA in the liver and the vascular territory to be treated may occur in a small percentage (\4 %) of cases and can be explained by different injection rates and different arterial flow between soluble contrast molecules versus 99m Tc-MAA, or to different locations of the microcatheter tip between the diagnostic phase and the treatment phase. Kao and colleagues [30] showed that 99m Tc-MAA SPECT/CT more accurately represents hepatic microparticle biodistribution than does soluble contrast hepatic angiography. Alternatively, the tumor may have an unidentified accessory arterial blood supply or may have caused vascular remodeling of the local arteries.…”
Section: Hepatic Perfusion Imagingmentioning
confidence: 99%